MARKETING MIX STRATEGY TO ATTRACT CUSTOMER INTEREST IN USING SAVINGS PRODUCTS AT BANK SYARIAH INDONESIA - Agrosamdhyo, Raden (widya balina, 2026)
This research analyzes the implementation of the 7P marketing mix framework—comprising product, price, place, promotion, people, process, and physical evidence—at Bank Syariah Indonesia (BSI) to attract consumer interest in adopting sharia-compliant savings products within an increasingly volatile banking environment. Amidst accelerating retail competition following consolidated structural expansions, the main objective of this study is to trace the relationship between strategic structural integration and retail consumer acquisition dynamics. The methodology incorporates a qualitative case study paradigm operating primarily through continuous field observations at physical institutional touchpoints combined with an extensive evaluation of web-based portal data and corporate disclosures. The key findings reveal that the proactive orchestration of zero-administration deposit schemes, transparent sharia-compliant pricing margins, broad multi-channel distribution, targeted digital netnography campaigns, and highly optimized automated mobile routing systems collectively acts as a core catalyst for amplifying consumer market trust and broadening retail account portfolios. The study concludes that the seamless integration of digital service architectures with traditional branch infrastructures under sharia tenets remains vital for maintaining structural growth and securing long-term institutional presence in competitive regional commercial banking fields.